2022
DOI: 10.1002/cncy.22581
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphologic features of SMARCA4‐deficient non–small cell lung carcinoma and correlation with immunohistochemical and molecular features

Abstract: BACKGROUND: SMARCA4/BRG1-deficient tumors and those that have loss of SMARCA/BRG1 have been described as various aggressive carcinomas and sarcomas, including a subset of non-small cell lung carcinoma (NSCLC). Cytomorphologic features of NSCLCs are yet to be described. The objective of this study was to evaluate the cytomorphologic features, immunohistochemical profile, and molecular profile of SMARCA4/BRG1-deficient NSCLC (SMARCA4-dNSCLC). METHODS:The authors retrospectively searched for cases with SMARCA4/BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This finding is consistent with the findings of our study because dominant single‐cell pattern was significantly more frequent in cytology specimens of TSDUT, but we did observe a dominant single‐cell pattern in a minority of SD‐NSCLC cases. Furthermore, Sun et al 24 . reported dominant single‐cell pattern in two cases of SD‐NSCLC, further highlighting that this feature is not exclusive to TSDUT.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the findings of our study because dominant single‐cell pattern was significantly more frequent in cytology specimens of TSDUT, but we did observe a dominant single‐cell pattern in a minority of SD‐NSCLC cases. Furthermore, Sun et al 24 . reported dominant single‐cell pattern in two cases of SD‐NSCLC, further highlighting that this feature is not exclusive to TSDUT.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, Sun et al 24 reported dominant single-cell pattern in two cases of SD-NSCLC, further highlighting that this feature is not exclusive to TSDUT.…”
Section: Discussionmentioning
confidence: 91%
“…Although as a novel disease entity, undifferentiated NSCLC with SMARCA4-deficient/TP53 mutations has already been deemed to be highly aggressive disease, rarely response to current treatment schedules, and extremely poor prognosis. [14][15][16] A retrospective research by Massachusetts General Hospital was performed to assess the clinical features of patients with tumors harboring SMARCA4/BRG1-inactivating mutations. They have detected SMARCA4 genomic alterations in 9% (n = 117 of 1422) and 11% (n = 3188 of 27,281) of NSCLC in the institutional and foundation medicine data sets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports and studies have reported the clinicopathologic features of SMARCA4 -dNSCLC ( 1 , 3 , 14 ). SMARCA4 -dNSCLC is a heterogenous group in terms of cytomorphology, ranging from a relatively well-differentiated adenocarcinoma pattern or squamous differentiation to an undifferentiated morphology ( 1 , 3 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information available regarding the imaging characteristics of SMARCA4 -dNSCLC. Moreover, patients with SMARCA4 -dNSCLC respond poorly to conventional therapeutic approaches, further complicating treatment ( 2 , 3 ). Here, we present a case of a 52-year-old male with SMARCA4 -dNSCLC and a review of the relevant literature.…”
Section: Introductionmentioning
confidence: 99%